Left ventricular remodelling patterns in patients with moderate aortic stenosis . (18th February 2022) - Stassen, Jan; Ewe, See Hooi; Hirasawa, Kensuke; Butcher, Steele C; Singh, Gurpreet K; Amanullah, Mohammed R; Sin, Kenny Y K; Ding, Zee P; Pio, Stephan M; Chew, Nicholas W S; Sia, Ching Hui; Kong, William K F; et al.
Abstract: Aims : Moderate aortic stenosis (AS) is associated with an increased risk of adverse events. Because outcomes in patients with AS are ultimately driven by the condition of the left ventricle (LV) and not by the valve, assessment of LV remodelling seems important for risk stratification. This study evaluated the association between different LV remodelling patterns and outcomes in patients with moderate AS. Methods and results : Patients with moderate AS (aortic valve area 1.0–1.5 cm 2 ) were identified and stratified into four groups according to the LV remodelling pattern: normal geometry (NG), concentric remodelling (CR), concentric hypertrophy (CH), or eccentric hypertrophy (EH). Clinical outcomes were defined as all-cause mortality and a composite endpoint of all-cause mortality and aortic valve replacement (AVR). Of 1931 patients with moderate AS (age 73 ± 10 years, 52% men), 344 (18%) had NG, 469 (24%) CR, 698 (36%) CH, and 420 (22%) EH. Patients with CH and EH showed higher 3-year mortality rates (28% and 32%, respectively) when compared with patients with NG (19%) ( P < 0.001). After multivariable adjustment, CH remained independently associated with mortality (HR 1.258, 95% CI 1.016–1.558; P = 0.035), whereas both CH (HR 1.291, 95% CI 1.088–1.532; P = 0.003) and EH (HR 1.217, 95% CI 1.008–1.470; P = 0.042) were associated with the composite endpoint of death or AVR. Conclusion : In patients with moderate AS, those who develop CH already have an increased risk of all-cause mortality. Assessment of the LV remodelling patterns may identify patients at higher risk of adverse events, warranting closer surveillance, and possibly earlier intervention. Graphical Abstract: